2007
DOI: 10.28945/138
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Communication Styles, Trust, and Satisfaction in Virtual Teams

Abstract: Previous studies have identified the difficulty of communicating in virtual teams. The lack of media richness, or opportunity for using non-verbal cues, leads to misunderstood communications and may limit the development of trust. Studies have also shown that males and females are socialized to communicate differently. Males use communication in teams to establish dominance and position while females use it to establish relationships and gain trust. In this study, we analyzed whether the gender of individual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
(52 reference statements)
2
20
0
2
Order By: Relevance
“…So, because males are less comfortable with visual contact, its absence should help them to achieve a better understanding of the counterpart, and higher quality agreements as a result. This hypothesis is consistent with findings showing that males perceive eye contact as more threatening than females (Dalton, Nacewicz, Johnstone, Schaefer, Gernsbacher, Goldsmith, Alexander, & Davidson, 2005) and that males feel the loss of visual contact to a lesser extent than females (Furumo & Pearson, 2007).…”
Section: The Moderating Role Of Sexsupporting
confidence: 81%
“…So, because males are less comfortable with visual contact, its absence should help them to achieve a better understanding of the counterpart, and higher quality agreements as a result. This hypothesis is consistent with findings showing that males perceive eye contact as more threatening than females (Dalton, Nacewicz, Johnstone, Schaefer, Gernsbacher, Goldsmith, Alexander, & Davidson, 2005) and that males feel the loss of visual contact to a lesser extent than females (Furumo & Pearson, 2007).…”
Section: The Moderating Role Of Sexsupporting
confidence: 81%
“…Previous research on gender differences in virtual teams by Furumo and Pearson (2007) shows that women experience more trust than men, and men have less ability to dominate team interactions. It may be that women project managers are experiencing less embedded gender bias (Ridgeway, 2011) in virtual space than on ground.…”
Section: Women Project Managersmentioning
confidence: 96%
“…Multiple studies have identified gender differences in communication style (e.g., [28,29]). For instance, scholars have found that communication from men tends to be more task-oriented (i.e., informative) while women tend to adopt more socially-oriented (i.e., sociable) communication styles [30][31][32].…”
Section: Hypothesis 4 (H4)mentioning
confidence: 99%